2016
DOI: 10.1016/j.molp.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane H + -ATPase Regulation in the Center of Plant Physiology

Abstract: The plasma membrane (PM) H(+)-ATPase is an important ion pump in the plant cell membrane. By extruding protons from the cell and generating a membrane potential, this pump energizes the PM, which is a prerequisite for growth. Modification of the autoinhibitory terminal domains activates PM H(+)-ATPase activity, and on this basis it has been hypothesized that these regulatory termini are targets for physiological factors that activate or inhibit proton pumping. In this review, we focus on the posttranslational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
354
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(365 citation statements)
references
References 106 publications
(143 reference statements)
9
354
0
2
Order By: Relevance
“…Thr881 is situated in the conserved autoinhibitory region I of the C-terminal domain of AHA2 (Rudashevskaya et al , 2012; Falhof et al , 2016), and rapid PLANT PEPTIDE CONTAINING SULFATED TYROSINE 1 (PSY1)-induced in planta phosphorylation of AHA2 at Thr881 increases proton efflux (Fuglsang et al , 2014). To assess the role of AHA2 in growth inhibition upon mild osmotic stress, we characterized the strong knock-down aha2-4 mutant with only ~10% AHA2 expression compared to the wild type (Haruta et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Thr881 is situated in the conserved autoinhibitory region I of the C-terminal domain of AHA2 (Rudashevskaya et al , 2012; Falhof et al , 2016), and rapid PLANT PEPTIDE CONTAINING SULFATED TYROSINE 1 (PSY1)-induced in planta phosphorylation of AHA2 at Thr881 increases proton efflux (Fuglsang et al , 2014). To assess the role of AHA2 in growth inhibition upon mild osmotic stress, we characterized the strong knock-down aha2-4 mutant with only ~10% AHA2 expression compared to the wild type (Haruta et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Cell wall acidification mediated by plasma membrane H + -ATPases (Falhof et al, 2016) stimulates expansins due to their low-pH optima (Cosgrove, 2016b) and is also the driving force for solute uptake to generate cell turgor.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the activation of MHA1 occurs by another mechanism, or this isoform has another binding site for 14-3-3 proteins (Portillo, 2000). The protein kinase responsible for the phosphorylation of Thr947 H + -ATPase has not yet been identified (Gaxiola, Palmgren, and Schumacher, 2007;Falhof, Pedersen, Fuglsang, and Palmgren, 2016). Recently additional sites of phosphorylation have been revealed (Rudashevskaya et al, 2012;Haruta, Gray, and Sussman, 2015;Falhof, Pedersen, Fuglsang, and Palmgren, 2016).…”
Section: Regulation Of Plasma Membrane H + -Atpase At Post-translatiomentioning
confidence: 99%
“…The protein kinase responsible for the phosphorylation of Thr947 H + -ATPase has not yet been identified (Gaxiola, Palmgren, and Schumacher, 2007;Falhof, Pedersen, Fuglsang, and Palmgren, 2016). Recently additional sites of phosphorylation have been revealed (Rudashevskaya et al, 2012;Haruta, Gray, and Sussman, 2015;Falhof, Pedersen, Fuglsang, and Palmgren, 2016). Among those sites were Ser-899, Ser-904 and Ser-931 residues in AHA1 and AHA2 proteins of Arabidopsis.…”
Section: Regulation Of Plasma Membrane H + -Atpase At Post-translatiomentioning
confidence: 99%